Investigating the Role of Medical Terms Translation in Facilitating Learning Process for Medical Students - Abdelrahman Elyass Mohamed Abdelmajd; Hassan Mahill Abdallah Hassan (Yayasan Visi Intan Permata, 2017)
This paper aims to answer “To what extent Medical Terms Translation can help in Facilitating Learning Process for Medical Students?” The researcher has adopted the quantitative method as well as the questionnaire as a tool for collecting data relevant to the study to bring to the light the importance of Medical Terms Translation in Facilitating Learning Process for students who study Medical Sciences. The sample of this study comprises (60) students. The marks obtained from the questionnaire were compared. From one hand, the results have revealed that the students encountered difficulties in understanding the Medical Terms. The result has shown that the questionnaire significance indicates that there is highly difference among students. Therefore, this indicates that Medical Terms Translation can play great role in Facilitating Learning Process for Students who study Medical Sciences.